Predictive value of 3′-deoxy-3′-18F-fluorothymidine PET in the early response to anti-programmed death-1 therapy in patients with advanced non-small cell lung cancer. Issue 7 (22nd July 2021) - Sato, Masayuki; Umeda, Yukihiro; Tsujikawa, Tetsuya; Mori, Tetsuya; Morikawa, Miwa; Anzai, Masaki; Waseda, Yuko; Kadowaki, Maiko; Kiyono, Yasushi; Okazawa, Hidehiko; Ishizuka, Tamotsu
Abstract : Background: Anti-programmed death-1 (anti-PD-1) therapy has shown clinical success in patients with advanced non-small cell lung cancer (NSCLC). However, it is difficult to evaluate the early response to anti-PD-1 therapy. We determined whether changes in 3′-deoxy-3′-[ 18 F]-fluorothymidine ( 18 F-FLT) PET parameters before and soon after treatment initiation predicted the therapeutic effect of anti-PD-1 antibody. Methods: Twenty-six patients with advanced NSCLC treated with anti-PD-1 antibody were enrolled prospectively and underwent 18 F-FLT PET before and at 2 and 6 weeks after treatment initiation. Changes in maximal standardized uptake value (ΔSUVmax ), proliferative tumor volume (ΔPTV) and total lesion proliferation (ΔTLP) of the lesions were calculated and evaluated for their associations with the clinical response to therapy. Results: The disease control rate was 64%. Patients with non-progressive disease (non-PD) had significantly decreased TLP at 2 weeks, and decreased SUVmax, PTV, and TLP at 6 weeks, compared with those with PD, while three of eight (37.5%) patients who responded had increased TLP from baseline at 2 weeks (ie, pseudoprogression). Among the parameters that changed between baseline and 2 weeks, ΔPTV0-2 and ΔTLP0-2 had the highest accuracy (76.0%) to predict PD. Among the parameters that changed between baseline and 6 weeks, ΔSUVmax 0-6, ΔPTV0-6 and ΔTLP0-6 had the highest accuracy (90.9%) to predict PD. ΔTLP0-2 (≥60%, HR 3.41, 95% CI 1.34–8.65, p=0.010) and ΔTLP0-6 (≥50%, HR 31.4, 95% CI 3.55 to 276.7, p=0.0019) were indicators of shorter progression-free survival. Conclusions: Changes in 18 F-FLT PET parameters may have value as an early predictive biomarker for the response to anti-PD-1 therapy in patients with NSCLC. However, it should be noted that pseudoprogression was observed in 18 F-FLT PET imaging at 2 weeks after treatment initiation. Trial registration number: jRCTs051180147.